Umbilical Nodule Metastasis from Unknown Primary: Diagnostic and Therapeutic Dilemma - Gupta, Sweety; Sharma, Gaurav; Sharma, Nidhi; Mandal, Shreyosi; Gupta, Amit; Gupta, Manoj (The Surgery Journal, 2022)
Umbilical nodule metastasis is not a common presentation of carcinoma of unknown primary. It may be the presenting symptom of a primary malignancy or as metastatic site of previously diagnosed cancer and is considered to be a poor prognostic finding. We here report a case of young male who presented with umbilical mass, but the primary could not be localized even after thorough investigations and work up. Also, there existed therapeutic dilemma because immunohistochemistry did not favor one site, and so he was considered for combination chemotherapy in view of unresectable disease.
Keywords: umbilical; metastases; palliative chemotherapy; unknown primary